Analisis Biomekanika dan Beban Kerja pada Pekerja Pemecah Batu Tradisional di Grindulu, Tegalombo, Pacitan - Lorenza, Aditya; Hendrawan, Aloysius Tommy; Untari, Erny (Jurnal TRINISTIK: Jurnal Teknik Industri, Bisnis Digital, dan Teknik Logistik, 2023)
In industries that still use human power to move materials, even though some relatively modern industries have used machines as a tool for moving materials, manual material handling (MMH) is still very necessary because it has advantages compared to using tools, namely. Manual material handling usually occurs in confined spaces and where workers rely heavily on the human body to lift items, but if manual material handling (MMH) is not carried out ergonomically, accidents can occur. Damage to body tissue due to removal. The method used in this research is a questionnaire based on the NBM (Nordic Body Map). Regarding the worker's position, RWL (Recommended Weight Limit) is a method used to explain some movement errors in traditional stone body presses. From the results of the analysis of the Grindulu River for two Tegalombo stone crushers, Pacitan, the results were good or there was no potential for injury because the results were less than 1, namely the value for worker 1 was 0.162 (Good) and worker 2 was 0.384 (Good). obtained from distributing questionnaires from 2 respondents on the banks of the Grindulu river, Tegalombo, Pacitan, conclusions can be drawn. 1. Using Biomechanical forces on organisms and investigating the interaction effects of body forces, including forces arising from inside and outside the body, workers do not experience potential injury and produce a score below 1 (Good). Keywords: Biomechanics, Material Handling Manual, Nordic Body Map, Recommended Weight Limit